An Assessment of Availability and Utilization of Internet Resources for Final Year Students Research Project in Nigeria Tertiary Institutions - Ime Robson Nseobot; Mansoor Ahmed Soomro; Godwin Donatus James (International Journal of Organizational Business Excellence, 2021)
The research aims to examine the availability of internet resources for studenta’ final projects at tertiary institutions in Nigeria. The craving for the Internet stems from its central role in ICT with access to free online journals, magazines, and other information resources anytime and from anywhere for academic and research purposes. University undergraduates are required to do research during their final year of university. Writing projects are required prior to the award of tertiary degrees in Nigeria. Project writing is regarded as being important by every student. Research project writing involves a student or group of students carrying out a study on a topic of interest. When the project is finished, it is assessed by the work that was completed on time, which indicates the student's ability to select, research, and draw logical conclusions from findings. Resources consulted and cited are greatly impacted by the quantity, quality, and recency of the resources consulted and cited. The research finds that the internet plays a major role in helping undergraduate researchers' access large number of materials from different parts of the globe.